Medical treatment - Castro Bianchino, Omar (Cirugía del Uruguay, 1971)
Modifications of the thrombophilic state can be attempted through the following resources: - Oral anticoagulants do not modify structural hypercoagulability. Its action on platelet hyperadhesivity is random and only palliative and indirect on kinetic hypercoagulability. - Heparin corrects all tendencies of the thrombophilic state ...